Impact of lifestyle and socio-economic factors on household carbon in Iskandar, Malaysia [electronic resource] - Seyed Nima Moeinzadeh Mirhosseini, 1983- author; Mohammad Rafee, supervisor; Irina Safitri Zen, supervisor; Fakulti Alam Bina (2015)
Thesis (Ph.D (Perancangan Bandar dan Wilayah)) - Universiti Teknologi Malaysia, 2015